Our History ( Strathmore ) : Strathmore through the last 60 years - Silvano Borruso - Strathmore, University (Strathmore University, 2018)
Mr. Silvano Borruso. 1st Bursar Strathmore School. He was one of the first members of Opus Dei that St. Josemaria sent to begin the Work in Kenya. He arrived in September of 1960. Watch out to have deeper insight of the Strathmore Journey through 60 years as its told by Sivano Borruso.